Democratic Policing, Building Trust, and Willingness to Call 911: Examining the Relationship between Law Enforcement Legitimacy and Calling the Police - McLean, Kyle (American journal of criminal justice, 2024)
Recent debates over policing have centered on the proper role of policing in society. Using the lenses of democratic policing and police legitimacy, we suggest that individuals’ willingness to call the police is one method for understanding the public’s consent to be policed and their view of the appropriate role of policing. This simple relationship is further complicated by differential relationships between willingness to cooperate with the police and four typologies of police legitimacy: trustworthiness, normative alignment, obligation to obey, and traditional legitimacy. Using the pretest and posttest of a survey vignette, we show that (1) individuals who legitimate the police on the basis of their traditional role in society are more likely to call the police for benign issues, (2) officer-involved shootings negatively impact individuals’ willingness to call the police, and (3) there is a greater reduction in willingness to call the police following an officer-involved shooting when individuals legitimate the police on the basis of perceived normative alignment.